O enquadramento multimodal da morte dos jornalistas na cobertura da tragédia da Chapecoense nos sites da RBS TV, do Foxsports.Com.Br e do Globoesporte.com - Torres, Alexsandro de Oliveira (2020)
This dissertation discusses how the death of the 20 journalists on the LaMia flight, which crashed near Medellín airport in Colombia, was reported and killed 71 people, including media professionals, the Chapecoense football delegation and guests on November 29th, 2016. The present research is conducted by two central objectives: 1) understand how journalists manifested themselves in the stories, identifying how they expressed emotions about what happened; 2) understand how the journalistic agent was noticed on the scene and how narratives about Rafael Henzel, the only professional from press who survived the plane crash, were framed. In order to answer these questions, online journalism was chosen as an object of investigation, as it mainly understands that this digital territoriality gathers news in the form of texts, photographs, audios and videos, which are constantly updated, which gather vast material about the flight crash. Under the hypothesis of a subportrayal of the death of journalists and an appreciation of the rhetoric of solidarity with Chapecoense, three sites of journalistic organizations that had more professionals among the fatal victims of the accident were chosen as corpus of analysis: Foxsports.com.br; Globoesporte.com; and the RBS TV website. The methodological procedure adopted for this research was the multimodal framework, which included textual, visual and narrative analysis of a total of 489 articles collected from the three journalistic sites between November 29th, 2016 and December 11th of the same year. Firstly, the methodology was applied to seek an understanding of how the journalistic coverage of the air accident as a whole was carried out, in particular to examine the multimodal framework regarding the news about the death of the 20 journalists. The results obtained by the investigation show, even with some peculiarities between the three sites, the affection policy around Chapecoense as the dominant line of stories, including comparisons with other tragedies in the world of sports. However, the same procedure was not verified to emphasize that the death of the 20 press professionals in the fall of the LaMia flight represented the biggest accident involving Brazilian journalists in history, surpassing, in quantitative numbers, the 14 deaths of professionals from four television stations. caused by the explosion of an aircraft that collided with a hill near the city of Macaé, in Rio de Janeiro, on June 28, 1984. There was also a difficulty, or even a possible lack of interest, in the national press, in a way in general, to talk about the professional of another journalistic organization, thus giving ample emphasis to their own employees during the news. However, it would be improper to attest that all the mass media devalued the death of journalists in the fall of the LaMia flight, so there is a need to promote more research in order to be able to analyze and debate, more regularly, the journalistic practices employed by the Brazilian press.